(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Alcoholism is a chronic disease. It has been observed that alcoholism runs in families! India lies 4th in the 5-point scale for Years of Life Lost scale of WHO. It ranges from uncontrolled drinking and pre-occupation with alcohol. An alcoholic is a man or a woman who suffers from alcoholism - they have a distinct physical desire to consume alcohol beyond their capacity to control it, regardless of all rules of common sense. Symptoms include repeated alcohol consumption despite related legal and health issues. Those with alcoholism may begin each day with a drink, feel guilty about their drinking and have the desire to cut down on the amount of drinking. There are Various factors have been associated with alcoholism and this study was conducted with the aim to find out psychosocial factors in the alcoholic individual with objectives to find out simple explanation for why some individuals develop problems with alcohol. Multiple biological and psychosocial factors mutually influence each other in causing alcohol abuse; it would be incorrect to view psychosocial causes as either independent from, or competing with, biological causes. Rather, alcohol use and alcoholism are best viewed as end products of a combination of bio psychosocial influences. In India, there are more than 10 million cases of alcoholism per year which makes the issue grave to be taken into account.